1997
DOI: 10.1128/jvi.71.9.6407-6415.1997
|View full text |Cite
|
Sign up to set email alerts
|

Shared usage of the chemokine receptor CXCR4 by the feline and human immunodeficiency viruses

Abstract: Feline immunodeficiency virus (FIV) induces a disease state in the domestic cat that is similar to AIDS in human immunodeficiency virus (HIV)-infected individuals. As with HIV, FIV can be divided into primary and cell culture-adapted isolates. Adaptation of FIV to replicate and form syncytia in the Crandell feline kidney (CrFK) cell line is accompanied by an increase in the net charge of the V3 loop of the envelope glycoprotein, mirroring the changes observed in the V3 loop of HIV gp120 with the switch from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(95 citation statements)
references
References 56 publications
8
85
2
Order By: Relevance
“…After 48 h of coculture, cells were stained for b-galactosidase activity and scored for syncytia formation. This cellcell fusion assay is based on the facts that the FIV Petaluma isolate is independent of the CD134 primary receptor for cell entry (Shimojima et al, 2004) and that FIV can efficiently use human CXCR4 (Poeschla and Looney, 1998;Willett et al, 1997). Under the experimental conditions described above, 293T cells expressing wild-type Env yielded 763769 blue syncytia per well (average of three independent experiments,7SD).…”
Section: Cell-cell Fusion Mediated By Mutant Fiv Env Glycoproteinsmentioning
confidence: 99%
“…After 48 h of coculture, cells were stained for b-galactosidase activity and scored for syncytia formation. This cellcell fusion assay is based on the facts that the FIV Petaluma isolate is independent of the CD134 primary receptor for cell entry (Shimojima et al, 2004) and that FIV can efficiently use human CXCR4 (Poeschla and Looney, 1998;Willett et al, 1997). Under the experimental conditions described above, 293T cells expressing wild-type Env yielded 763769 blue syncytia per well (average of three independent experiments,7SD).…”
Section: Cell-cell Fusion Mediated By Mutant Fiv Env Glycoproteinsmentioning
confidence: 99%
“…vaccination) would provide the virus with an ideal opportunity for its replication [109]. Furthermore, the FIV coreceptor CXCR4 molecule is expressed on activated T-, B-cells and monocytes [110]. It was demonstrated that increased expression of CXCR4 in cell lines resulted in enhanced FIV replication in vitro [111].…”
Section: Fiv Vaccine Candidatesmentioning
confidence: 99%
“…One possible reason for the existence of polymorphisms is that polymorphisms might prevent pathogens from binding to receptors and using them as an entry point into cells. Several G protein-coupled receptors have been used by pathogens as a point of entry into cells and the use of CCR5 and CXCR4 as co-receptors for HIV-1 and CXCR4 as a co-receptor for FIV are notable examples [14][15][16]. The CCR5 receptor in African green monkeys [17] has been shown to be polymorphic and these polymorphisms provide some protection against SIV infection.…”
Section: Introductionmentioning
confidence: 99%